IMPLEMENTASI WORDWALL DALAM MATERI PERUBAHAN ENERGI UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV DI SDN 2 SONOKULON - Aini, Rosita Nur; Nurmawati, Fulusia; Nurwulandari, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This class action research aims to improve student learning outcomes in Natural and Social Science subjects by using WordWall. This class action research was carried out at SDN 2 Sonokulon. The subjects of this study are class V students totalling 16 students. The class action research model used in this study is the Kemmis and Mc model. Taggart. Data on student learning outcomes in the learning of Natural and Social Education Sciences in cycle I reached 37.5% and in cycle II has met the achievement criteria set with student learning outcomes in cycle II reaching 87.5% with an average of 62.5%. The result of the teacher's action monitoring instrument in cycle I was 82.15% while in cycle Il reached 98.21% with an average of 90.18%. The result of student activity instrument in cycle I is 50% while in cycle I it reaches 93.75% with an average of 71.88%. The conclusion from this study is that the implementation of WordWall media in the learning of Natural and Social Sciences can improve the learning outcomes of students in class V of SDN 2 Sonokulon, so that teachers can use WordWall learning media as one of the alternatives to improve student learning outcomes in learning Natural and Social Sciences.